2012
DOI: 10.1103/physrevd.85.024032
|View full text |Cite
|
Sign up to set email alerts
|

Gravity dual of the Ising model

Abstract: We evaluate the partition function of three dimensional theories of gravity in the quantum regime, where the AdS radius is Planck scale and the central charge is of order one. The contribution from the AdS vacuum sector can -with certain assumptionsbe computed and equals the vacuum character of a minimal model CFT. The torus partition function is given by a sum over geometries which is finite and computable. For generic values of Newton's constant G and the AdS radius ℓ the result has no Hilbert space interpre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
168
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(186 citation statements)
references
References 75 publications
14
168
2
Order By: Relevance
“…11) compared to the simulation without obliquity dependency, and, hence, to an effective acceleration parameter of η e 0.15. Therefore, there is a lower amount of CRs produced in the shock, and as expected from Chevalier (1983) (see also Castro et al 2011;Bell 2015), the exact solution is now better reproduced for a lower effective adiabatic index of γ e = 1.55 (see Fig. 12) and leads to a shock front in advance compared to the obliquity-independent simulation.…”
Section: The 3d Sedov Explosionmentioning
confidence: 66%
See 1 more Smart Citation
“…11) compared to the simulation without obliquity dependency, and, hence, to an effective acceleration parameter of η e 0.15. Therefore, there is a lower amount of CRs produced in the shock, and as expected from Chevalier (1983) (see also Castro et al 2011;Bell 2015), the exact solution is now better reproduced for a lower effective adiabatic index of γ e = 1.55 (see Fig. 12) and leads to a shock front in advance compared to the obliquity-independent simulation.…”
Section: The 3d Sedov Explosionmentioning
confidence: 66%
“…There is a large body of evidence for CRs accelerated in the shocked-shell material of supernova (SN) explosions (e.g. Koyama et al 1995;Decourchelle et al 2000;Aharonian et al 2004;Warren et al 2005;Helder et al 2009;Ackermann et al 2013) and it is shown that they have a significant impact on the shell structure and dynamics (Chevalier 1983;Dorfi 1990;Zank et al 1993;Wagner et al 2009;Ferrand et al 2010;Castro et al 2011;Pfrommer et al 2017;Pais et al 2018;Diesing & Caprioli 2018). SN remnants (SNR) are expected to be the main source of CRs permeating the entire interstellar medium (ISM) of galaxies (Aguilar et al 2015), though the consistency of the accelerated CR spectrum in SNR with that of entire galaxies is still intensely debated (see Blasi 2013 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…The equations of motion (4.1) are then recognized as the Lax equations 20) where the subindex + indicates the truncation to non-negative powers of ∂ + only. The factor of µ can be absorbed into a redefinition of x − .…”
Section: Commuting Charges From the Kdv Hierarchymentioning
confidence: 99%
“…Partition functions have been computed in [15,16], and three point functions have been checked in [7,[17][18][19]. Other aspects of the duality have been investigated extensively [20][21][22][23][24][25], see [26] for a review.…”
Section: Introductionmentioning
confidence: 99%
“…This is very similar in spirit to the proposal of[10] to compute partition functions from vacuum characters.…”
mentioning
confidence: 55%